Analisis Determinan Demografi dan Sosial terhadap Preferensi Lokasi Pemeriksaan Kesehatan Remaja : Studi Data SKI 2023 - Ricko Pratama Ridzkyanto; Nida Ardelia Rosyida; Yunita Safa Bela (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Adolescence is a critical period for shaping health behaviors, especially in terms of accessing preventive health care. The health service achievement for elementary school-aged students in East Java Province in 2023 was 100.9%, and in 2024, 99.2%. The purpose of this study was to analyze the relationship between demographic and social factors and the Selection of Health Check-up Locations for Adolescents in East Java Province. This study is quantitative, cross-sectional, and uses secondary data from the 2023 Indonesian Health Survey (SKI). The study sample consisted of 35,344 adolescents aged 15-18 years. The independent variables in this study were age, gender, education, and occupation, while the dependent variable was the location of the health check-up. Data analysis included univariate, bivariate, and multivariate analyses using Logistic Regression. The results showed relationships between age (0.001), gender (0.001), and occupation (0.030) and the location of the health check-up, and no relationship between education (0.076) and the location of the health check-up. The most dominant variable influencing the location of health check-ups was occupation, with an OR of 1.371 (95% CI = 1.031–1.822). It is recommended that the timing of health check-ups be adjusted to adolescents' working hours.